A Fully Functional Universal Self‐Chargeable Power Module for Portable/Wearable Electronics and Self‐Powered IoT Applications. Issue 48 (30th October 2020) - Maharjan, Pukar; Bhatta, Trilochan; Cho, Hyunok; Hui, Xue; Park, Chani; Yoon, Sanghyuk; Salauddin, Md; Rahman, Muhammad Toyabur; Rana, SM Sohel; Park, Jae Y.
Abstract: Realization of self‐charging, miniaturized, portable, high output, and sustainable energy harvesting devices with wide application areas and good storage under a realistic environment remains a challenge. Herein, a universal self‐chargeable power module (USPM) is presented that can efficiently harvest human bio‐mechanical energy, ocean wave blue energy, and automobile vibration energy. By implementing a multiple spring‐based mechanical coupling design, the hybrid electromagnetic‐triboelectric generator shows high performance despite miniaturization under very low acceleration (≤1 g) and low frequency (≤6 Hz) vibration. The electromagnetic performance is further optimized by using a soft magnetic material‐based flux concentrator while electrospun nanofibers enhance the triboelectric performance. The USPM is a compactly designed device including a power management circuit, a battery charging circuit, built‐in rechargeable storage, and a USB‐C outlet, providing a direct current power of maximum 34.11 mW. Experimental results show remarkable performance in the context of harvesting biomechanical energy from walking, running, cycling and demonstrates real‐time charging of smartphones, earbuds, and smart bands. Similarly, it demonstrates the capability of harvesting blue energy and powering a wireless water health monitoring system using a polyaniline/laser‐induced graphene/polydimethylsiloxane based pH sensor. Moreover, it successfully scavenges automobile vibration energy and demonstrates a self‐powered wireless in‐car environment monitoring system. Abstract : A universal self‐chargeable power module is newly developed to efficiently harvest random low frequency and low acceleration vibration energy from human motion, water‐wave motion, and automobile vibration. By implementing multiple spring mechanical coupling, flexible flux‐concentrator, and electrospun nanofibers, the module delivers a high direct current output power of 34.11 mW which can easily power wearable/portable electronics and sensors.